Spectral-ellipsometric examining the films of gold nanoparticles on Si/SiO₂ substrate - Bortchagovsky, E.G.; Lozovski, V.Z.; Mishakova, T.O.; Hingerl, K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
We have investigated optical properties of films of gold nanoparticles on Si/SiO₂ substrate by using the method of spectroscopic ellipsometry in dependence on morphology of the films. Different morphology of the films was obtained by flashannealing at various temperatures of identical sputtered thin gold layers. Ellipsometric spectra were compared with account of pictures of the films obtained by scanned electron microscopy. Remarkable dependence of depolarization of the reflected light with the frequency of localized plasmon resonance versus the film morphology was found.